Impact of Assessment Technique on Learning Outcomes:A Case Study - Nethravathi, S.; Chaitanya, L. (Journal of Engineering Education Transformations, 2018)
In order to achieve excellence, it is important for the educational institutions to assess the outcomes of their graduate programmes. In general, the graduate programme outcomes are assessed through direct assessments such as internal tests, quizzes, projects, assignments etc. and indirect assessments such as exit survey. The Course Outcomes are assessed through direct and indirect assessment techniques such as course end surveys. The results through direct assessment are followed up with several actions such as remedial classes, tutorials etc. Feedback surveys from the students, recruiters and alumni are considered for the indirect assessment of Programme outcomes. In this paper, the methodology adopted for the assessment of Course Outcomes for Microcontrollers course are presented.